2022
DOI: 10.1128/spectrum.01700-22
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production by Facultative Anaerobic Wood-Rot Fungi via a New Halomethane-Dependent Pathway

Abstract: Here, we demonstrate that wood-rot fungi produce methane anaerobically without the involvement of methanogenic archaea via a new, halomethane-dependent pathway. These findings of an anaerobic fungal methane formation pathway open another avenue in methane research and will further assist with current efforts in the identification of the processes involved and their ecological implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…Before the studies by [17] and [18], which found that saprotrophic fungi directly produce CH4 under aerobic conditions without the presence of methanogenic archaea, it was assumed that fungi initiated the decomposition process by breaking down macromolecules, like those in wood, thereby providing the precursor compounds for CH4 production by methanogenic archaea in anoxic microsites (e.g., [20][21][22][23]). Another CH4 producing pathway, involving facultative anaerobic fungi and a halomethane dependent pathway, was identified by [24], where CH4 formation correlated with the formation of chloromethane (CH3Cl), as previously reported by [25]. These authors further highlight, that the function of the enzymes involved in the halomethane dependent CH4 formation pathway are independent of O2 and thus might also be involved in observed fungal CH4 production by [17] and [18].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Before the studies by [17] and [18], which found that saprotrophic fungi directly produce CH4 under aerobic conditions without the presence of methanogenic archaea, it was assumed that fungi initiated the decomposition process by breaking down macromolecules, like those in wood, thereby providing the precursor compounds for CH4 production by methanogenic archaea in anoxic microsites (e.g., [20][21][22][23]). Another CH4 producing pathway, involving facultative anaerobic fungi and a halomethane dependent pathway, was identified by [24], where CH4 formation correlated with the formation of chloromethane (CH3Cl), as previously reported by [25]. These authors further highlight, that the function of the enzymes involved in the halomethane dependent CH4 formation pathway are independent of O2 and thus might also be involved in observed fungal CH4 production by [17] and [18].…”
Section: Introductionsupporting
confidence: 68%
“…While the exact mechanism of CH4 formation by these fungi remains elusive, initial evidence by [17], which identified methionine as a precursor of fungal CH4, suggests that the universal CH4 formation mechanism proposed by [10] involving Fenton chemistry with methylated compounds and ROS likely represents a significant contributor to the observed CH4 formation. Nonetheless, the potential involvement of other mechanisms, such as the halomethanedependent pathway reported by [24], cannot be ruled out. Although demonstrated under anaerobic conditions, the activity of the relevant enzymes for this mechanism also persists under aerobic conditions, presenting another possible CH4 formation mechanism that warrants future investigation, particularly under aerobic conditions.…”
Section: Dependence Of Fungal Ch4 Formation On O2 Levelsmentioning
confidence: 96%
“…enzymes for this mechanism also persists under aerobic conditions, presenting another possible CH4 formation mechanism that warrants future investigation, particularly under aerobic conditions. (upper part) and Huang et al [24] (lower part). The upper part illustrates the mechanisms proposed for CH4 formation driven by reactive oxygen species (ROS) in living systems, which involves the production of methyl radicals via Fenton chemistry from methylated compounds.…”
Section: Dependence Of Fungal Ch 4 Formation On O 2 Levelsmentioning
confidence: 96%
“…Before the studies by Lenhart et al [17] and Schroll et al [18], which found that saprotrophic fungi directly produce CH 4 under aerobic conditions without the presence of methanogenic archaea, it was assumed that fungi initiated the decomposition process by breaking down macromolecules, like those in wood, thereby providing the precursor compounds for CH 4 production through methanogenic archaea in anoxic microsites (e.g., [20][21][22][23]). Another CH 4 -producing pathway involving facultative anaerobic fungi and a halomethane-dependent pathway was identified by Huang et al [24], where CH 4 formation correlated with the formation of chloromethane (CH 3 Cl), as previously reported by McNally et al [25]. These authors further highlighted that the function of the enzymes involved in the halomethane-dependent CH 4 formation pathway is independent of O 2 and thus might also be involved in the observed fungal CH 4 production by Lenhart et al [17] and Schroll et al [18].…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, S. commune possesses special energy generation processes through ethanol fermentation and amino acid metabolism, as well as an increase in mitochondrial number [ 12 , 13 ]. It also has complex nitrogen conversion mechanisms under anaerobic conditions and the ability to degrade difficult-to-degrade macromolecules such as lignite, resulting in the production of methane and extracellular polysaccharides [ 14 16 ]. Simonato et al reported that the yeast Saccharomyces cerevisiae can modify its membrane composition to tolerate high hydrostatic pressure [ 17 ].…”
Section: Introductionmentioning
confidence: 99%